2018
DOI: 10.1007/s00128-018-2441-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity and Hazardous Concentrations of Zinc to Native Freshwater Organisms Under Different pH Values in China

Abstract: Zinc bioavailability to aquatic organisms varies greatly under different pH values. In the present study, five native species in China and four common international test species were selected to investigate the influence of changing pH on acute zinc toxicity. The results showed that the higher trophic levels exhibited increasing sensitivity to zinc as pH decreased. However, when the pH value was between 8 and 11, the acute toxicity of zinc was relatively constant. In addition, by using a species-sensitivity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Zinc (Zn) is a nutritional trace element essential for living animals, including aquatic animals [ 14 ], however, excessive Zn concentrations can be toxic [ 15 , 16 ]. Zinc oxide nanoparticles (ZnO-NPs) are inorganic compounds with a wide range of applications in various industries from cosmetics to wastewater treatment [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc (Zn) is a nutritional trace element essential for living animals, including aquatic animals [ 14 ], however, excessive Zn concentrations can be toxic [ 15 , 16 ]. Zinc oxide nanoparticles (ZnO-NPs) are inorganic compounds with a wide range of applications in various industries from cosmetics to wastewater treatment [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zn is involved in the nucleic acid synthesis, the immune system, and neurotransmission (MacDonald, 2000). However, at higher concentrations, it can be toxic to fish (Li et al, 2019), and can be a modifier of the carcinogenic response (Bostanci et al, 2016). In humans, acute Zn poisoning may result in nausea, vomiting, diarrhea and fever (Agnew and Slesinger, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Zinc is an essential trace element for aquatic organisms and humans however high concentrations of zinc may cause adverse effects to the organisms [12][13][14][15]. Zinc toxicity to the microalgae Scendesmus obliquus was reported by Li et al [16] with LC50/EC50 value ranged between 0.057-0.217 mg/l. The effect of zinc and manganese on the microalgae Pavlova viridis was studied by Li et al [17,18] and the increase in antioxidant enzyme activity indicated the oxidative stress caused by the metals.…”
Section: Discussionmentioning
confidence: 99%